2016
DOI: 10.1149/2.0591607jes
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Operational Parameters on Lithium Deposition in Lithium-Ion Cells: Systematic Measurements with Reconstructed 3-Electrode Pouch Full Cells

Abstract: Deposition of metallic Li is a severe aging mechanism in Lithium-ion cells. This study evaluates the influence of the main operating parameters leading to deposition of Li: temperature, charging C-rate, and end-of-charge voltage. Therefore both, graphite anodes and NMC cathodes from commercial 16Ah pouch cells are reconstructed into 3-electrode full cells Due to their comparably high energy and power densities, Lithiumion batteries are currently used in state-of-the-art electric cars.1-3 In automotive applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
135
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 159 publications
(142 citation statements)
references
References 40 publications
7
135
0
Order By: Relevance
“…Below 0 V versus Li/Li + , Li metal deposition on the anodes surface becomes thermodynamically possible . Li deposition is a severe side reaction, which is caused by overpotentials favored by charging at low temperatures, high current densities, and high lithiation states . Li metal deposition on anodes leads to fast aging by reaction with the electrolyte .…”
Section: Introductionmentioning
confidence: 99%
“…Below 0 V versus Li/Li + , Li metal deposition on the anodes surface becomes thermodynamically possible . Li deposition is a severe side reaction, which is caused by overpotentials favored by charging at low temperatures, high current densities, and high lithiation states . Li metal deposition on anodes leads to fast aging by reaction with the electrolyte .…”
Section: Introductionmentioning
confidence: 99%
“…7,16,18,20,27 In this case the anode potential vs. Li/Li + is mostly positive. 20,22 In contrast, critical combinations of low temperatures, high charging C-rates, and high SOCs lead to negative anode potentials vs. Li/Li + and therefore to deposition of metallic Li on graphite anodes, often called Li plating. [20][21][22][23][24][28][29][30] Due to the high reactivity of Li metal and the possibility of forming mechanically decoupled Li, cycling under Li plating conditions leads to fast capacity fade.…”
mentioning
confidence: 99%
“…20,22 In contrast, critical combinations of low temperatures, high charging C-rates, and high SOCs lead to negative anode potentials vs. Li/Li + and therefore to deposition of metallic Li on graphite anodes, often called Li plating. [20][21][22][23][24][28][29][30] Due to the high reactivity of Li metal and the possibility of forming mechanically decoupled Li, cycling under Li plating conditions leads to fast capacity fade.a Present address: BMW AG, D-80788 München, Germany. z E-mail: thomas.waldmann@zsw-bw.de However, there is still a dearth of knowledge on the effect of aging mechanisms on the safety properties of Li-ion cells.…”
mentioning
confidence: 99%
“…A previous study with the same cell type showed that charging at C/25 does not lead to negative anode potentials vs. Li/Li + and therefore no Li deposition is expected. 18 Standard electrochemical measurements are performed in order to characterize cells before dismantling. Cells are discharged at a rate of C/10 until 2.7 V is reached.…”
Section: Methodsmentioning
confidence: 99%